Younger people are more vulnerable to stress, anxiety and depression during COVID-19 pandemic: A global cross-sectional survey - Varma, Prerna; Junge, Moira; Meaklim, Hailey; Jackson, Melinda L. (Progress in neuro-psychopharmacology & biological psychiatry, 2021)
The COVID-19 pandemic has had far-ranging consequences for general physical and mental health. Country-specific research reveals a general reduction in mental and physical well-being, due to measures undertaken to stop the spread of COVID-19 disease. However, research is yet to examine the impact of the pandemic on global psychological distress and its effects upon vulnerable groups. Exploration of the factors that potentially mediate the relationship between stress and mental health during this period is needed, to assist in undertaking concrete measures to mitigate psychological distress and support vulnerable groups. Therefore, this study examined the impact of the COVID-19 pandemic on psychological distress globally, and identified factors that may exacerbate decline in mental health. N = 1653 participants (mean age 42.90 ± 13.63 years; 30.3% males) from 63 countries responded to the survey. Depression and anxiety were assessed using the Patient Health Questionnaire and State Trait Anxiety Inventory, respectively. Other measures included the Perceived Stress Scale, the Pittsburgh Sleep Quality Index, 3-item UCLA Loneliness Scale and the Brief Resilient Coping Scale. Globally, consistently high levels of stress, anxiety, depression and poor sleep were observed regardless of number of COVID-19 cases. Over 70% of the respondents had greater than moderate levels of stress, with 59% meeting the criteria for clinically significant anxiety and 39% reporting moderate depressive symptoms. People with a prior mental health diagnosis experienced greater psychological distress. Poor sleep, lower levels of resilience, younger age and loneliness significantly mediated the links between stress and depression, and stress and anxiety. Age-based differences revealed that younger age-groups were more vulnerable to stress, depression and anxiety symptoms. Results show that these vulnerable individuals need more support. Age-specific interventions for modifiable factors that mediate the psychological distress need to urgently deployed to address the global mental health pandemic. •Respondents from over 60 countries endorsed significant symptoms of anxiety, stress, and depression.•Psychological distress was driven by poor sleep, isolation, low resilience and age.•While older adults are more vulnerable to the virus, younger adults are at a greater risk of poor mental health.•Perceived stress, financial uncertainty was linked to poor mental health in young adults.•There is an urgent need for sustained, global public health measures to mitigate the psychological effects.